IMPACT-INDUCED PERTURBATIONS OF ATMOSPHERIC SULFUR - Kring D.A.; Melosh H.J.; Hunten D.M. (My University, 1996)
Asteroids and comets that are vaporized during hypervelocity impact events can inject large masses of S into the stratosphere where it can potentially affect the radiation budget of the Earth, alter the chemistry of the ozone layer, and eventually be converted to sulfuric acid rain. Relatively small carbonaceous asteroids, 0.3 km in diameter, contain 5 times more S than the entire modern stratosphere and these objects hit the Earth at an average rate of 1 per 10,000 years. Larger impact events, capable of injecting 1015 g of S into the stratosphere, occur at an average rate of 1 per 1 million years. Calculations indicate there is sufficient O and H in the vapor plumes of most impact events to convert the S to sulfuric acid aerosols. If this conversion occurs, then the larger impact events could depress mean surface temperatures by more than 2oC for 3 years or longer.
Keywords: IMPACTS; ASTEROIDS; ATMOSPHERE; SULFUR